Kedudukan Anak Non Muslim Terhadap Harta Warisan Ditinjau dari Kompilasi Hukum Islam - Nizmah Nizmah (Fakultas Syariah IAIN Laa Roiba Bogor, 2019)
The noble Qur'an has explained the laws of inheritance, the conditions of each heir with a sufficient explanation, where no one among humans escapes the inheritance or inheritance. Because the Qur'an is the backing in establishing the law and the extent of its parts. And very few are determined based on Sunnah or ijma. there is no position of nonMuslim children on inheritance in compilation of Islamic law. While the Religious Court is a court that has the authority to examine and try inheritance disputes for people who are Muslim. Thus, if there is a dispute over inheritance issues between children of Muslims and non-Muslims, it must be resolved through the Religious Courts. Formulation of the problem in this study is how the position of non-Muslim children on the inheritance of Islamic heirs is reviewed from the Compilation of Islamic Law. with literature analysis it means that the author takes data based on existing literature. Based on the results of the study, according to the Compilation of Islamic Law dividing inheritance to the entitled heirs is the obligation of heirs to the heir to be implemented after the heirs have carried out other obligations as contained in. The position of nonMuslim children on the inheritance of Islamic heirs based on Islamic law does not obtain inheritance from the inheritance of their parents. According to the Compilation of Islamic Law as in the case of the Religious Court, it shows that the position of non-Islamic children on inheritance from the inheritance of the property of their parents does not receive the right inheritance, but based on the Religious High Court, get a section called